Propriedades tecnológicas da madeira de clones de Eucalyptus spp. - Talgatti, Maiara (2017)
This study aimed to examine lumber physical properties, mechanical, performance and quality during air-drying and anatomy of fibers of six Eucalyptus spp clones. The clones were obtained from commercial planting with spacing of 2 x 3 meters located in the followings cities: Capivari do Sul, state of Rio Grande do Sul, Paragominas, state of Pará and Telêmaco Borba, state of Paraná, with 6 – 11 age range. In order to do so, were made, from six trees of each specie/hybrid, samples for each physical test, mechanical, drying and anatomy of fibers. The evaluation of the physical and mechanical properties were made by the D143-94 - ASTM (2005) standard. Boards of 2,54 x 10,00 x 1,20, cm were used for the air drying process. Posteriorly, the drying defects and timber top cracks were analyzed. The preparation of macerated boards followed the method Nitric-Acetic Acid. The overall average of basic density of species/hybrid was 0,4394 g.cm-3. Thus, the lumber can be described, generally, as a lightweight material. The species used in this study have from medium to low retractability woods, being within the limits of the literature for the genus Eucalyptus spp., the anisotropic factor indicates that the woods have normal performance. In the mechanical tests, it was possible to analyze that, higher specific masses did not implied in higher MOE and MOR and the Eucalyptus can be considered, in general, as resistant to impacts and resilient. In the outdoor drying tests, the drying curves of eucalyptus wood did not presented constant drying rate, which allows characterize the species as impermeable. Despite the wood of clone 1006 be characterized as medium density, this clone presented the highest drying rate, contrary to what was expected in the literature. About the lumber quality, the clone 1006 was considered the one with the best performance in relation to the appearance of top cracks, but it was the one of worse quality about the incidence of defects after drying. The choice of the best tree, which presented less defects, was made in relation to the bending because this defect is the worst of all and almost irreversible. This way, in this respect, Clone 1005 was considered the best quality for sawn products. For the anatomical study of the fibers, it was observed values of the Runkel index greater than 1, these are more indicated for the production of absorbent papers. However, for a safe recommendation of the species / hybrids for this purpose, it is important that a chemical analysis of their wood be carried out. Finally, the clones studied presented potential for multiple use due to the variability observed between them.